Perang Global Melawan Terorisme dalam Perspektif Sekuritisasi - Dina Yulianti (Jurnal ICMES, 2017)
The Global War on Terrorism has continued 17 years since 2001 but has not made the world safer. Terrorist acts continue to occur in various countries, even new terrorist groups have emerged, including IS (Islamic State). US presidents from the George W. Bush to Trump continue to declare terrorism as a threat for national security and world security. This article discussed this phenomenon using securitization theory to answer the question of whether terrorism really threatens US security or is there other factors behind the continuity of GWOT policy? The study found that although acts of terrorism did caused many victims, the casualties of GWOT are much greater. The US goal in launching GWOT is to frighten the world (using the ‘politics of fear’) so that countries are willing to join GWOT's military operations. This war is very profitable for the US military industry and escalate US domination in the world.